Chapter 9 Emotions and Sexuality Regulation and Homoerotic Transgression - Grassi, Umberto (Taylor & Francis, 2019)
The Routledge History of Emotions in Europe: 1100-1700 presents the state of the field of pre-modern emotions during this period, placing particular emphasis on theoretical and methodological aspects of current research. Exploring topics such as love, war, sex and sexuality, death, time, the body and the family in the context of emotional culture, The Routledge History of Emotions in Europe: 1100-1700 reflects the sharp rise in scholarship relating to the history of emotions in recent years and is an essential resource for students and researchers of the history of pre-modern emotions.